PENGARUH PEMBERIAN BEBERAPA JENIS PUPUK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KAILAN (Brassica alboglabra L.) - Dede Haryadi; Husna Yetti; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Kailan included in a group of vegetables that have high economic value. Kailan low production occurred due to good soil physical, chemical and biological of soil due to the loss of nutrients in the soil. The addition of nutrients in the soil to increase crop production kailan can be done by way of fertilization. Fertilization can be done with use of organic fertilizers and inorganic fertilizers. The aims of this research are to determine the effect of some types fertilizer on the growth and yield of kailan and to obtain the best dose of treatment. This research was conducted experimentally by using completely randomized design (CRD) factorial with consisted of 5 treatments and 3remedial. The result of research show suggest that administering some kind of fertilizer for crops kailan significant on plant height, plant fresh weight, weight of plants suitable for consumption and the ratio of the root crown , but not significant on the number of leaves. NPK fertilizer with a dose of 0.025 kg/m2 is the best treatment to improve growth and crop production kailan.   Key Word :Some types of fertilizer, Kailan